Mechanism of High Frequency Shallow Earthquake Source in Mount Soputan, North Sulawesi - Suparman, Yasa; Kriswati, E.; Pamitro, Y. E. (Indonesian Journal on Geoscience, 2011)
DOI:Â 10.17014/ijog.v6i3.122Moment tensor analysis had been conducted to understand the source mechanism of earthquakes in Soputan Volcano during October - November 2010 period. The record shows shallow earthquakes with frequency about 5 - 9 Hz. Polarity distribution of P-wave first onset indicates that the recorded earthquakes are predominated by earthquakes where almost at all stations have the same direction of P-wave first motions, and earthquakes with upward first motions.In this article, the source mechanism is described as the second derivative of moment tensor, approached with first motion amplitude inversion of P-wave at some seismic stations. The result of moment tensor decomposition are predominated by earthquakes with big percentage in ISO and CLVD component. Focal mechanism shows that the recorded earthquakes have the same strike in northeast-southwest direction with dip about 400 - 600. The sources of the high frequency shallow earthquakes are in the form of tensile-shear cracks or a combination between crack and tensile faulting.